Airbone Hydrographic Surveys in the Canadian Arctic - Eaton, R. M. (The International Hydrographic Review, 2015)
"None of us had ever seen waters so absolutely impossible to navigate as this Sound." This was how the Norwegian explorer Sverdrup described Hell Gate, in the Canadian Arctic Archipelago, when he discovered it in 1899. That he later sailed through it in a ship's boat illustrates the way in which the Arctic becomes less forbidding on acquaintance. In 1960 the hydrographic section of the Polar Continental Shelf Project began to survey the predominately ice covered waters of the Archipelago north of Parry Channel (parallel of 75° N), and in three years covered 190 000 sq. km of sea with soundings spaced 2-10 km apart. This was reconnaissance work, but techniques were evolved which will lead to the attempt, in 1963, to survey Hell Gate to normal standards of accuracy and thoroughness solely by airborne methods; the survey should be finished before the arrival of an icebreaker on her annual passage to re-supply the weather reporting station at Eureka, 350 km further north. This article describes the environment; echo sounding through ice; profile sounding by towing from a helicopter in open water; and position fixing in helicopters.